Endoscopic Treatment of Colonic Duplication Cyst: A Case Report and Review of the Literature. (13th February 2018) - Garg, Rajat; Saravolatz, Louis D.; Barawi, Mohammed
Abstract : Colonic duplication cysts are a rare congenital abnormality commonly presenting before two years of age. In adults, it has been rarely reported, most often as an incidental finding. We report a case of 42-year-old female complaining of constipation and lower abdominal pain. Patient's CT scan of the abdomen showed a cystic lesion at hepatic flexure and the diagnosis was confirmed endoscopically using endoscopic ultrasound (EUS). The cyst was treated employing hot snare to expose the cyst cavity. On our literature search, there have been no reported cases of colonic duplication cyst treated endoscopically. We here discuss incidence, diagnosis, characteristics, and treatment of duplication cysts with special emphasis on endoscopic therapy.